Network Pharmacology Study on the Underlying Mechanism of Danggui–Kushen Herb Pair in Adjuvant Chemotherapeutics against Breast Cancer - Hu, Yijuan; He, Jiaolong; Xu, Yunling (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundThe Danggui–Kushen herb pair (DKHP) is a classic prescription that has long been used in combination with chemotherapeutic drugs to improve the immune status of patients with breast cancer (BC), however, the active components and the underlying pharmacological mechanisms remain unclear. Therefore, this study aimed to elucidate the possible mechanism of action of DKHP against BC-based comprehensive strategy combining network pharmacology, molecular docking, and cellular experiments.MethodsThe Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform was used to obtain the relevant compounds in DKHP. Genecards and the National Center for Biotechnology Information databases were used to predict BC targets. Then, drug–compound–target, and protein–protein interaction networks were constructed to forecast the promising protein targets of DKHP and identify the primary interactions that occur between the protein targets and compounds. Finally, the predicted candidate targets were validated using docking techniques and in vitro experiments.ResultsA total of 30 potential active compounds and 173 intersecting pharmacological targets were identified in DKHP. Gene Ontology enrichment analysis revealed that the inflammatory response, positive regulation of protein phosphorylation, and cellular response to lipopolysaccharide were closely related to DKHP treatment in BC. Kyoto Encyclopedia of Genes and Genomes pathway analysis suggested that the PI3K/AKT pathway may be crucial for DKHP intervention in BC. Therefore, key targets could be AKT1, TP53, VEGR, CASP3, TNF, and IL6. Molecular docking analysis suggested that hyperforin, kushenin, and kushenol T had good binding ability to Akt, p53, and Caspase 3. The in vitro experiment showed that the DKHP extract promoted the apoptosis of MCF-7 cells via the PI3K/Akt signaling pathway. These results corresponded to the predictions produced using the network pharmacology approach.ConclusionHyperforin, kushenin, kushenol T, and other active compounds in DKHP can regulate multiple signaling pathways and targets, such as AKT1, TP53, and CASP3, thereby playing preventive and therapeutic roles in BC.
Keywords: Network pharmacology